Kegiatan Pemberdayaan Masyarakat Melalui Pelatihan Copywriting Bagi UMKM di Kota Semarang - Lianna Wijaya; Rini Kurnia Sari; Noor Udin; Taufiq Annas; Hendri Hartono (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Community service activities are very important to improve the quality of human resources for MSMEs. Copywriting training was conducted by Bina Nusantara University Semarang for 30 MSMEs in the city of Semarang. The term copywriting was not yet known to the participants and this training was attended with great enthusiasm so that the participants could increase their knowledge regarding marketing using copywriting techniques which are one of the trends in the marketing world. Training participants are expected to have the ability to write attractive promotional or advertising language so that their products can stick in the minds of customers. By mastering this copywriting technique, the participants are able to increase product sales through digital marketing via social media by using advertising writing techniques that are attractive to the customers.